A Case of Septic Shock Due to Serratia marcescens Pyelonephritis and Bacteremia in a Patient Receiving Empagliflozin. (December 2017) - Kufel, Wesley D.; Scrimenti, Ali; Steele, Jeffrey M.
Sodium–glucose cotransporter 2 (SGLT2) inhibitors have been associated with serious urinary tract infections (UTIs) including pyelonephritis and urosepsis. The Food and Drug Administration (FDA) issued a label change to include this warning in December 2015 due to a small number of cases (n = 19) reported to the FDA Adverse Event Reporting System. Details of these cases are limited and none involved empagliflozin. To date, there has been no published literature comprehensively describing serious UTIs attributed to empagliflozin. We describe a case of septic shock due to Serratia marcescens pyelonephritis and bacteremia that required intensive care unit admission in a well-controlled, type 2 diabetic patient who had begun taking empagliflozin 2 months prior. The patient was treated successfully with intravenous antibiotics followed by oral ciprofloxacin. After discontinuation of empagliflozin and completion of antibiotic therapy, no subsequent UTIs were documented in the following 4 months.